Immigrant voices in Indian-American literature: a study of the selected works of Bharati Mukherjee, Chitra Banarjee Divakurani and Jhumpa Lahiri - Marzita Mohamed Noor (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2012)
This thesis analyses the immigrant voices in Indian-American literature. My objective is to investigate texts by three American women writers of Indian background: Bharati Mukhe1:jee (1940-), Chitra Banm:jee Divakaruni (1956-) and Jhumpa Lahiri (1967-). These women writers share similar themes and concerns in their works which make them ideal writers for this study. The works I have chosen for interrogation are The Al/idd!eman and Other Stories (1988) and .Jasmine ( 1989) by Bharati Mukhe1:jee,Arranged Marriage ( 1995) and The Mistress <~l Spices (1997) by Chitra Banarjee Divakaruni, and Interpreter ofMaladies (1999) and The Namesake (2003) by Jhumpa Lahiri. The study purports to see if the perceptions and imagination of these immigrant/diasporic writers contribute to our understanding of the immigrant experience itself The study is based on a qualitative research. It is crucial to determine whether "displaced" Indian writers enable readers to relate to the immigrant experiences better as only an immigrant would be able to empathise with the plight, anxiety and ambivalence of other immigrants. Part of the thesis is also focused on gender discourse as the writers under scrutiny are female writers, and their fictions are often populated by female characters. The fears and traumas experienced by these female migrants in their culturally uprooted circumstance, their process of reconciliation with the new culture, and their overall representation in the works of these women writers have been researched at length in this thesis. The themes and concerns of Indian-American writers are otlen different from the mainstream American writers as their works deal with multiculturalism, cultural clashes and hybridity, identity crisis, displacement and nostalgia, among others. My theoretical fi:amework employs the post-colonial theory as the main theory. I will also apply the diaspora theory and Third World Feminist theory on the works. The post-colonial theory is used because the books are post-colonial in nature. The diaspora theory is used to show the issues of diaspora and its effects on identity and character. The Third World feminist theory is used because many of the characters in the fictions are female, and so are the authors. Their works are crucial as examples of women who have triumphed in the process of assimilation, among others.